Compatibility Analysis of Silicon Nitride and Silicon Dioxide on HCI induced LDD MOSFET - Haziezol Helmi bin Mohd Yusof, H.H.M.Yusof; Norhayati binti Soin, N.Soin; Nissar, Nissar M.K.; Sufyan, M.Sufyan; Faiz bin Arith, Faiz Arith (American-Eurasian Networks for Scientific Informations (AENSI), 2014)
Hot-carrier-injection (HCI) is one of important reliability issue under short-channel effect in modern MOSFET devices especially in nano-scaled CMOS technology circuits. The effect of the hot carrier can be reduced by introducing Lightly-Doped-Drain (LDD) structure on the device. The objective of this project is to study the effect of hot carrier in the LDD n-MOSFET. The LDD n-MOSFET is stressed with bias voltage at intervals of stressing time to determine the degradation model in the threshold voltage and drain current. From the parametrical analysis, it shows that the shift in threshold voltage and degradation in the drain current occurred after the MOSFET device is stressed with hot carrier stress test. The rate of threshold voltage shift and degradation of the drain current are dependence to the stressing time applied to the MOSFET device. The hot carrier stress test shows that the device with Si3N4 has smaller voltage shift compared to SiO2 material.